Searches for lepton-flavour-violating decays of the Higgs boson into eτ and μτ in s $$ \sqrt{s} $$ = 13 TeV pp collisions with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Hadron-Hadron Scattering.; Springer Open.